Severe bacterial infections in people who inject drugs: the role of injection-related tissue damage - Alexander Hrycko; Pedro Mateu-Gelabert; Courtney Ciervo; Rebecca Linn-Walton; Benjamin Eckhardt (BMC, 2022)
Abstract Background In the context of the current U.S. injection drug use epidemic, targeted public health harm reduction strategies have traditionally focused on overdose prevention and reducing transmission of blood-borne viral infections. Severe bacterial infections (SBI) associated with intravenous drug use have been increasing in frequency in the U.S. over the last decade. This qualitative study aims to identify the risk factors associated with SBI in hospitalized individuals with recent injection drug use. Methods Qualitative analysis (n = 15) was performed using an in-depth, semi-structured interview of participants admitted to Bellevue Hospital, NYC, with SBI and recent history of injection drug use. Participants were identified through a referral from either the Infectious Diseases or Addition Medicine consultative services. Interviews were transcribed, descriptively coded, and analyzed for key themes. Results Participants reported a basic understanding of prevention of blood-borne viral transmission but limited understanding of SBI risk. Participants described engagement in high risk injection behaviors prior to hospitalization with SBI. These practices included polysubstance use, repetitive tissue damage, nonsterile drug diluting water and multipurpose use of water container, lack of hand and skin hygiene, re-use of injection equipment, network sharing, and structural factors leading to an unstable drug injection environment. Qualitative analysis led to the proposal of an Ecosocial understanding of SBI risk, detailing the multi-level interplay between individuals and their social and physical environments in producing risk for negative health outcomes. Conclusions Structural factors and injection drug use networks directly impact drug use, injection drug use practices, and harm reduction knowledge, ultimately resulting in tissue damage and inoculation of bacteria into the host and subsequent development of SBI. Effective healthcare and community prevention efforts targeted toward reducing risk of bacterial infections could prevent long-term hospitalizations, decrease health care expenditures, and reduce morbidity and mortality.